Tuning the emissive characteristics of TADF emitters by fusing heterocycles with acridine as donors: highly efficient orange to red organic light-emitting diodes with EQE over 20%. Issue 29 (11th July 2019) - Chen, Tianheng; Lu, Chen-Han; Huang, Chih-Wei; Zeng, Xuan; Gao, Jie; Chen, Zhanxiang; Xiang, Yepeng; Zeng, Weixuan; Huang, Zhongyan; Gong, Shaolong; Wu, Chung-Chih; Yang, Chuluo
Abstract : Regulated by the fused heterocyclic units on the frame of acridine, two TADF emitters showed very different emissions from orange to pure red and excellent OLED performances. Abstract : The development of highly efficient orange-red organic thermally activated delayed fluorescence (TADF) emitters is currently challenging. Herein, we reported two new emitters, namely, BTDMAc-NAI andBFDMAc-NAI with benzofuran and benzothiophene fused to the acridine frame. Inspiringly, the target emitters showed very different emissions from orange to pure red, with the emission peak ofBTDMAc-NAI red-shifting to 650 nm. Meanwhile, these two emitters showed distinct TADF characteristics and high photoluminescence quantum yields (PLQYs). As a result, the orange-red OLED based onBFDMAc-NAI demonstrated an excellent performance with external quantum efficiency (EQE) beyond 20%. This work unveils the great potential of the fused polycycle molecular design in exploiting new orange-red TADF emitters for high-performance OLEDs.